Interventions to Reduce Intimate Partner Violence Perpetration by Men Who Use Substances: A Systematic Review and Meta-Analysis of Efficacy. (December 2021) - Stephens-Lewis, Danielle; Johnson, Amy; Huntley, Alyson; Gilchrist, Elizabeth; McMurran, Mary; Henderson, Juliet; Feder, Gene; Howard, Louise M.; Gilchrist, Gail
Introduction: Despite the high prevalence of intimate partner violence (IPV) perpetration by men who use substances, limited evidence exists about how best to reduce IPV among this group. Method: A systematic narrative review with meta-analysis determined the effectiveness of interventions to reduce IPV by men who use substances. Inclusion criteria were randomized and nonrandomized controlled trials; adult heterosexual male IPV perpetrators where at least 60% of participants were alcohol and/or drug users; the intervention targeted IPV with or without targeting substance use (SU); outcomes included perpetrator and/or victim reports of IPV, SU, or both. Methodological quality was assessed. Results: Nine trials ( n = 1, 014 men) were identified. Interventions were grouped into (1) integrated IPV and SU interventions ( n = 5), (2) IPV interventions with adjunct SU interventions ( n = 2), and (3) stand-alone IPV interventions ( n = 2). Cognitive behavioral and motivational interviewing therapies were the most common approaches. Data from individual trials showed a reduction in SU outcomes in the short term (≤3months; n = 2 trials) and IPV perpetration at different time points ( n = 3 trials) for interventions compared with treatment as usual (TAU). Meta-analysis with integrated IPV and SU interventions showed no difference in SU ( n = 3 trials) or IPV outcomes ( n = 4 trials) versus SU TAU. Conclusions: Little evidence exists for effective interventions for male IPV perpetrators who use substances. Outcomes in integrated interventions were not superior to TAU in meta-analysis. Future trials should consider the nature of the relationship between IPV and SU in intervention design, duration of intervention, and type and timing of outcome measures.